Customer expectation, satisfaction and loyalty among SA grocery retail - Dlamini, Mfundo Sicelo (My University, 2018)
ABSTRACT This study investigates the grocery retail sector in South Africa and what factors drive consumer behaviour. The literature emphasises the importance of understanding what shapes customer satisfaction and how this creates customer satisfaction that can then lead to customer loyalty. A quantitative approach was used for this study and questionnaires used to collect data. The study revealed that customer satisfaction was largely and solely impacted by expectation, the study investigated the impact of convenience, service, promotion, store atmosphere and expectation on customer satisfaction. Only expectation showed an impact on customer satisfaction, as satisfied customers displayed stronger loyalty behaviour. This was in line with the literature used in the compilation of the literature review and answered the overall research question of “Does customer satisfaction impact customer loyalty?” Future studies need to explore the gap in research of the impact of quality on customer satisfaction. An analysis of how the internet impacts the buying process also needs to be done as two thirds of purchases in the physical channel start online and there’s an advent of price comparison mechanisms.
Keywords: customer satisfaction, loyalty, expectation, convenience